Comparison of SCORE-Turkey and SCORE for high-risk countries: A cross-sectional analysis of patients presenting with initial episode of acute coronary syndrome - Deniz Demirci; Duygu Ersan Demirci (KARE Publishing, 2019)
Objective: This study was a comparison of the Systematic Coronary Risk Estimation for high-risk countries (SCORE-HRC), developed by the European Society of Cardiology (ESC) using data from 12 European cohort studies, and SCORE-Turkey, aimed at assessing the statin therapy protocol for primary prevention. Methods: A total of 323 patients who experienced their first episode of acute coronary syndrome were included in the study. The SCORE risk calculations were determined using age, sex, smoking status, blood pressure, total cholesterol, and high-density lipoprotein (HDL-C) level data. Statin treatment indications were evaluated according to the ESC guidelines (2016). Results: There was a significant difference in the statin indication ratio calculated using the SCORE-HRC and SCORE-Turkey formulae (42.7% and 39.0%, respectively; p=0.012). However, the recommendation to begin statin therapy was insufficient with both algorithms, according to the protocol of the ESC guidelines. There was also a significant difference between the 2 systems in the 10-year cardiovascular risk estimation (SCORE-HRC: 5.09+-4.67, SCORE-Turkey: 4.8+-4.67; p<0.001). The primary difference between the methods was related to HDL-C. The SCORE-HRC chart was more successful if the patient's HDL-C level was low. As the HDL-C level increased, the SCORE-Turkey formula performed better (p<0.001). According to the SCORE-HRC, 7.8% of the patients aged 50-59 years were in a 'very high-risk' group, while there were no patients aged <50 years in this group. Conclusion: The SCORE-HRC was superior to the SCORE-Turkey in patients with acute coronary syndrome. It is only appropriate to use the SCORE-Turkey algorithm for patients with a high HDL-C level. Nonetheless, the ESC SCORE classification is inadequate to determine the 'very high-risk' group based on this, ESC recommendations on initiation of statin therapy is insuffiecient particularly in those <60 years of age. The ESC risk classifications should be re-evaluated and a new algorithm should be developed for the Turkish community.